Diversity and abundance of primates and their threats in the interfluvium of the Napo and Putumayo rivers, Peruvian Amazonia - Aquino, Rolando (2016)
Within the northeastern Peruvian Amazonia remain areas with scarce information on primates, one of them being the interfluvium between the Napo and Putumayo rivers. This lack of information motivated us to conduct a study to determine the diversity and abundance of primates within the area, as well as to identify the threats, which inhibit these primate species populations. For this purpose, we conducted transect censuses in three sampling sites in October 2007, September 2013 and November 2014. In 1040 km of transect walks we observed 308 groups of nine primate species, the most common being Leontocebus nigricollis (109 groups) and the rarest being Alouatta seniculus (16 groups). Smaller groups of Lagothrix lagothricha lagothricha (8-11 individuals) and A. seniculus (3-5 individuals) were observed in Tamboryacu, a majorly disturbed sampling site. Likewise, the lowest population densities estimated for L. l. lagothricha and A. seniculus corresponded to this same sampling site with 3.8 indiv. /km2 and 1.6 indiv. /km2, respectively, while for the remaining species there were no major differences among the sampling sites. Among the activities, hunting and logging are the predominant threats responsible for the scarce populations of A. seniculus and l. l. lagothricha, mainly in the Napo River Basin.